Effect of environmental oxygen content on the oxide inclusion in laser solid formed AISI 420 stainless steel. (15th January 2016) - Song, Menghua; Lin, Xin; Liu, Fenggang; Yang, Haiou; Huang, Weidong
Abstract: A series of AISI 420 stainless steel samples were deposited under different oxygen partial pressures. The morphology, composition, size distribution and number density of the oxide inclusion were examined. Based on the thermodynamic calculation, the transformation process of the oxide inclusion was analyzed. Under air, the oxide inclusion comprised the angular spinel and allotriomorphic or globular compound oxide of spinel and silicate with large size. With decreasing the environmental oxygen content, the oxide inclusion became the globular oxide of mainly silicate with finer and more uniform size. The decrease of the O content in the sample mainly resulted in the decrease of the number density of the oxide particle but not the size. It is found that the oxide inclusion characteristics are determined mainly by the precipitation and solidification of the slag before and after the solidification of the liquid metal respectively. The size distribution of the oxide particle is dominated by the nucleation behavior when the O content is relatively low, while by the collision–coalescence behavior when the O content is high enough. The thermodynamic calculation can predict the oxide inclusion transformation reasonably for laser solid forming AISI 420 stainless steel. Graphical abstract: Highlights: Environmental oxygen content influences the oxide inclusion characteristics of the laser solid formed AISI 420 stainless steel. Thermodynamic calculations predict a reasonable transformation of the oxide inclusion for laser solid forming. The precipitation and solidification of the slag determine the oxide inclusion characteristics of the material.